Controle do pH no tubo digestivo de Aedes (Stegomyia) aegypti (Linnaeus, 1762) em diferentes condições fisiológicas - Denise Barguil Nepomuceno (2015)
Aedes (Stegomyia) aegypti is an important vector of several pathogens, such as yellow fever virus, dengue virus and more recently, chikungunya fever. Despite guts physiology and intestinal pH importance in digestion and probably for pathogens transmission, there are only a few studies about pH regulation in adult mosquitoes. Studies of digestive physiology in Lutzomyia longipalpis females showed they are able to adjust the intestinal pH and enzymatic activity according to the physiological state. In unfed sand flies, midguts pH is slightly acidic (pH 6,0), and after blood meal the abdominal midgut (where blood is stored to be digested) undergoes abrupt alkalinization until pH 8,15. The alkalinization mechanism is triggered by the presence of any protein or by free amino acids in high concentration inside midgut. This work aimed to study the hypothesis that hematophagous nematocerans have a mechanism of pH regulation similar to that seen in Lutzomyia longipalpis, since they have the same feeding pattern. We chose Aedes aegypti as a model to develop our study. We used H+-sensitive microeletrodes and indicator dyes to estimate intestinal pH of adult female A.aegypti submitted to different conditions: blood feeding, feeding on rich proteins solutions or amino acids solution, and feeding on solutions without proteins. Using buffered solutions provided by forced feeding, we observed that pH in unfed females midgut is acid (pH 6,0). In blood-fed female, pH in abdominal midgut reached a maximum pH of 7,8, while thoracic midgut remained acidic. Unlike L. longipalpis female, the mechanism by which A. aegypti females notice blood ingestion is linked to the perception of specific proteins found in plasma. These proteins belongs to the serpin family, proteins similar to ovalbumin, which was the only protein tested that was able to influence abdominal midguts pH. Alpha-glucosidase is a digestive enzyme responsible for sucrose digestion, a common sugar ingested by mosquitoes, and has an optimum pH near pH 6,0. According to our results, this enzyme activity was proportionally higher in thoracic midgut than in abdominal midgut. Therefore, A. aegypti also presents compartmentalization of blood and sugar digestion. Our results are in accordance to the hypothesis that hematophagous nematocerans have a similar digestive physiology.